Implementasi Teaching Factory Dalam Program LED Di Politeknik Sahid Jakarta (Studi Kasus Mahasiswa Program LED) - Nicko Gana Saputra; Baskoro Harwindito; Dadang Mardian (Jurnal Sains Terapan Pariwisata, 2021)
Teaching factory is a learning activity where the school carries out production or services that are part of the teaching and learning process. Production-based learning is a process of learning expertise or skills that are designed and implemented based on actual work procedures and standards to introduce to students how the world of work really is, so work-based learning is one of the best solutions. Politeknik Sahid Jakarta has a Leadership Entrepreneurship and Development (LED) program that implements teaching factory activities in teaching, where LED program students who act as members carry out hotel teaching activities just like hotels that have the purpose of knowing and describing the implementation of teaching factories in LED programs at Polytechnic Sahid Jakarta. This research is a qualitative-descriptive which uses observations and interviews as a method to collect data. The key informan is LED program student. The data results that have been collected will be described descriptively.